Anti-ultraviolet and anti-static modification of polyethylene terephthalate fabrics with graphene nanoplatelets by a high-temperature and high-pressure inlaying method. Issue 8 (April 2019) - Zhang, Cheng; Zhong, Ling; Wang, Dingfei; Zhang, Fengxiu; Zhang, Guangxian
Grafting graphene on polyethylene terephthalate (PET) fibers requires a large number of environmentally harmful chemicals. In this study, a facile high-temperature and high-pressure method of inlaying graphene nanoplatelets was applied to fabricate anti-ultraviolet (UV) and anti-static graphene/PET composites. The resulting graphene-inlaid (GI) PET fabric, which showed excellent anti-ultraviolet and anti-static properties, was characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, Fourier transform–infrared spectroscopy and X-ray diffraction. Results suggested that graphene had been inlaid into the PET fiber surface, and that the optimal inlaying conditions were as follows: inlaying temperature 200℃, inlaying pressure 15 MPa, and inlaying time 15 s. The UV protection factor of the GI PET fabric under optimal conditions could reach 50 + and was maintained at 50 + after 50 laundering cycles. The peak values of the static voltage and its half-time in the GI PET fabric could be reduced from 500.0 V to 10.0 V and from 7.39 s to 0.53 s, respectively, and the electrical resistivity of the GI PET fabric was 36.04 ± 0.14 kΩ . cm. The breaking strengths of the GI PET fabrics could be retained over 70.0% that of the pure PET fabric. The facile high-temperature and high-pressure inlaying method is an eco-friendly technique that requires very few chemicals, except for ethyl alcohol.